BIOLOGY AND GROWING OF TOMATO VARIETIES AND HYBRIDS (British Journal of Global Ecology and Sustainable Development, 2023)
Initially, the tomatoes were yellow, then they were brought to Europe, and already there, after a couple of hundred years, they acquired the familiar red color. Today in the world there are about 11 thousand varieties that differ in size, shape, and color. The article presents brief data on agricultural technology, varietal assessment based on the achievements of agricultural science, and the practice of the best seed farms.